Sprawozdawczość finansowa mikro jednostek w świetle dyrektywy 2013/34 UE = Financial reporting micro units in the light of Directive 2013/34 EU - Maciej Piechocki (Kazimierz Wielki University, 2016)
Piechocki Maciej. Sprawozdawczość finansowa mikro jednostek w świetle dyrektywy 2013/34 UE = Financial reporting micro units in the light of Directive 2013/34 EU. Journal of Education, Health and Sport. 2016;6(12):259-266. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.198478 http://ojs.ukw.edu.pl/index.php/johs/article/view/4052         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 09.12.2016. Accepted: 09.12.2016.     Sprawozdawczość finansowa mikro jednostek w świetle dyrektywy 2013/34 UE Financial reporting micro units in the light of Directive 2013/34 EU   Maciej Piechocki[1]   WSB Toruń, Katedra Finansów i Rachunkowości     Słowa kluczowe: Sprawozdawczość finansowa, mikro jednostka, dyrektywa 2013/34 UE Key words: Financial reporting, micro unit, Directive 2013/34 EU         Streszczenie Sprawozdawczość finansowa stanowi bardzo istotny element systemu informacji wewnętrznej i zewnętrznej. Niniejszy artykuł stanowi głos w dyskusji w procesie harmonizacji systemu sprawozdawczości dla grupy mikro podmiotów oraz dla podmiotów nie prowadzących ksiąg handlowych. W artykule zawarto sugestie praktyka gospodarczego i nauczyciela akademickiego w odniesieniu do przewidywanej modernizacji ustawy o rachunkowości z uwzględnieniem postanowień dyrektywy 2013/34 UE.           The financial reporting of the micro units in the light of Directive 2013/34 EU   Summary The financial reporting is a very important element of internal and external information. This article is a voice in the discussion in the process of harmonization of the reporting system for the group of micro-enterprises and entities that do not keep books of accounts. The article includes suggestions of economic practice and academic teacher in relation to the anticipated modernization of the Accounting Act to the provisions of Directive 2013/34 EU [1] dr Maciej Piechocki, WSB Toruń, Katedra Finansów i Rachunkowości